The Sonoscape of a Rural Town in the Mediterranean Region: A Case Study of Fivizzano - Almo Farina; Timothy C. Mullet (Acoustics, 2025)
The sonoscape of a small town at the foot of the Northern Apennines Mountains in north–central Italy was studied using a regular grid of automatic recording devices, which collected ambient sounds during the spring of 2024. The study area is characterized by high landscape heterogeneity, a result of widespread suburban agricultural abandonment and urban development. Sonic data were analyzed using the Sonic Heterogeneity Index and nine derivative metrics. The sonic signatures from 26 stations exhibited distinct, spatially explicit patterns that were hypothesized to be related to a set of 11 landcover types and seven landscape metrics. The unique sound profile of each sample site was consistent with the emerging heterogeneity of landcover typical of many Mediterranean regions. Some sonic indices exhibited stronger correlations with landscape metrics than others. In particular, the Effective Number of Frequency Bins Ratio (ENFBr) and Sheldon’s Evenness (E) proved particularly effective at revealing the link between sonic processes and landscape patterns. The sonoscape and landscape displayed correlations significantly aligned with their variability, highlighting the ecological heterogeneity of the sonic and physical domains in the study area. This case study underscores the importance of selecting appropriate metrics to describe complex ecological processes, such as the relationships and cause-and-effect dynamics of environmental sounds among human altered landscapes.